2022
DOI: 10.52842/conf.caadria.2022.1.019
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Collaborative Platform for E-learning: Analysis of Student Engagement and Perceptions

Abstract: In this paper, we discuss the potential of using virtual reality collaborative platforms for e-learning to improve the quality of online education. First, we explore the characteristics of existing online platforms that can be used for e-learning. Second, we present a method for creating a Virtual Reality Collaborative Environment (VRCE) for e-learning using an online platform, namely FrameVR. Third, an experiment is conducted to investigate participants' behavioural and emotional engagement when using Zoom an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Indeed, VR provides an immersive experience that induces in users a sense of realism, which improves the users' work efficiency and creativity [62]. Studies demonstrated that students are more engaged when using virtual reality collaborative tools than collaborative learning tools [63]. This is also due to the use of avatars that can help users to provide a sense of connectedness by promoting interaction with other avatars and presenting their opinion in virtual spaces [61,64].…”
Section: Discussion: How Advanced Tools Can Address Identified Challe...mentioning
confidence: 99%
“…Indeed, VR provides an immersive experience that induces in users a sense of realism, which improves the users' work efficiency and creativity [62]. Studies demonstrated that students are more engaged when using virtual reality collaborative tools than collaborative learning tools [63]. This is also due to the use of avatars that can help users to provide a sense of connectedness by promoting interaction with other avatars and presenting their opinion in virtual spaces [61,64].…”
Section: Discussion: How Advanced Tools Can Address Identified Challe...mentioning
confidence: 99%